Determinants of maternal satisfaction with focused antenatal care services rendered at public health facilities in the West Shewa Zone, Central Ethiopia: A multicentre cross-sectional study - Bekele, Gemechu Gelan; Seifu, Benyam; Roga, Ephrem Yohannes (Frontiers in Global Women's Health, 2023)
Background Every woman has the right to receive quality care during pregnancy. It is proven that antenatal care (ANC) reduces maternal and perinatal morbidity and mortality. The government of Ethiopia is also making intense efforts to increase the coverage of ANC. However, among pregnant women, the levels of satisfaction with the care provided are overlooked, as the percentage of women who complete all ANC visits is below 50. Therefore, this study aims to assess maternal satisfaction with ANC services rendered at public health facilities in the West Shewa Zone, Ethiopia. Methods A facility-based cross-sectional study was conducted among women who were receiving ANC in public health facilities in Central Ethiopia between September 1 and October 15, 2021. A total of 411 women were selected using the systematic random sampling method. The questionnaire was pretested and the data were collected electronically using CSEntry. The collected data were exported to SPSS version 26. The characteristics of the study participants were described using frequency and percentage. Bivariate and multivariate logistic regression were used to identify the factors associated with maternal satisfaction with focused ANC service. Result This study revealed that 46.7% [95% confidence interval (CI) (41.7%–51.6%)] of women were satisfied with ANC service. Factors such as the quality of the health institution [adjusted odd ratio (AOR) = 5.10, (95% CI: 3.33–7.75)], place of residence [AOR = 2.38, (95% CI: 1.21–4.70)], history of abortion [AOR = 0.19, (95% CI: 0.07–0.49)], and previous mode of delivery [AOR = 0.30, (95% CI: 0.15–0.60)] were significantly associated with women's satisfaction with focused ANC service. Conclusion More than half of pregnant women who received ANC were dissatisfied with the service they received. This should be a cause for concern, as the level of satisfaction is lower than that of the findings of previous studies conducted in Ethiopia. Institutional variables, interactions with patients, and previous experiences of pregnant women have an impact on the level of satisfaction. Due attention should be paid to primary health and communication of health professionals with pregnant women to improve the levels of satisfaction with focused ANC service.